Pemberdayaan Kelompok Tani Stroberi Melalui Pelatihan Storytelling Produk untuk Wisata Edukasi di Desa Pancasari - Kadek Ayu Ekasani; Ida Ayu Gayatri Kesumayathi; Putu Dian Yuliani Paramita; Ni Made Ayu Natih Widhiarini; Ni Putu Dian Nirmala Trisna; Anak Agung Intan Febrianti (Jurnal Pengabdian Masyarakat, 2026)
Pancasari Village in Buleleng Regency, Bali, is recognized as one of the main strawberry farming centers and a potential agrotourism destination based on educational tourism activities. Favorable geographical conditions, high-quality strawberry products, and strong community involvement constitute key assets for the development of community-based agrotourism. However, most strawberry farmers still face limitations in communication skills, particularly in presenting product values and production processes in an engaging, communicative, and contextual manner to visitors. This limitation has resulted in suboptimal tourist experiences, especially for visitors who seek direct interaction, cultural narratives, and meaningful explanations of local agricultural practices. This community service program aims to empower the strawberry farmer group in Pancasari Village through product storytelling training as a strategy to strengthen educational tourism attractiveness and enhance visitor experiences. The program was implemented using a participatory training approach, including initial observation, group discussions, hands-on practice, interaction simulations with tourists. The storytelling content focused on the origin of Pancasari strawberries, cultivation techniques, sustainability values, and local wisdom embedded in community farming practices. The results indicate a significant improvement in participants’ ability to structure coherent and engaging product stories that are easily understood by visitors. Farmers also demonstrated increased confidence in oral communication and improved skills in linking technical information with educational and cultural values. Overall, the program not only improved individual competencies but also reinforced the role of farmer groups as key actors in providing authentic educational tourism experiences.